Percepción ambiental de los pobladores del asentamiento humano Monte Sion sobre el manejo de los residuos sólidos domiciliarios distrito de San Juan Bautista, Loreto–Perú,2021 - Villalaz Fartolino, Karen Isabella (2023)
The general objective of the study presented was to know the perception of the residents on the topic already stated. It concerns a descriptive thesis and simple design. A sample of 124 people over 18 years of age who reside in the AAHH was considered. A survey was applied to collect data. The work reached the following conclusions: we worked with people who live in the community for more than 31 years and maintain 4 to 6 family members in their homes, interviewing men (66%) and women (44%), having as their main occupation , merchants, drivers, housewives, day laborers, etc. Regarding internalized environmental knowledge or personal knowledge about environmental problems and the environment, they refer that the environment is a set of factors such as water, air, soil, biodiversity and cultural elements that form the natural environment. Environmental problems affect these resources or the environment, such as the felling of forests alters the resource (72.6%), the growth of the vehicle fleet (80.6%), wastewater also (100%), the production of electrical energy 100% and the exploitation of hydrocarbons (88.7%). Regarding solid waste management, they stated that garbage is something that is thrown away and has no other use (40%), they deposit their waste in plastic bags (30%) and cardboard boxes (28.6%). There is no waste management in the homes (80%), it is only deposited and delivered to the RRSS collection units. They believe that poor municipal management causes waste pollution to occur in the community. They did not receive training on any topic in solid waste (100%) and 75.8% do not know what waste segregation means. They recognize organic waste (that decomposes, food remains) and inorganic waste (PETT plastics). They are willing to train in environmental issues, to have a healthy and harmonious environment.